Total, ageand sex-specific mortality after discharge of patients with heart failure: the first large-scale cohort real-world study on Russian population - A. E. Soloveva; A. E. Medvedev; A. V. Lubkovsky; A. I. Shmakov; A. E. Solovev; G. V. Endubaeva; T. V. Gorbacheva; O. Yu. Vaulina; P. S. Alekseev; Yu. E. Kurilyuk; S. V. Villevalde; N. E. Zvartau; et al. (Российский кардиологический журнал)
Aim. To assess total, ageand sex-specific survival rate after discharge of patients with heart failure (HF) using real-world electronic health data.Material and methods. This retrospective analysis of data from the St. Petersburg Chronic Heart Failure Registry was performed. Hospitalizations of patients aged 18 years with a diagnosis code I50.x (International Classification of Diseases, 10th revision) were included in the period from January 1, 2019 to December 31, 2023. Cases with acute myocardial infarction, cerebrovascular accident, coronavirus disease 2019, hospitalization duration of >30 days, and death during the current hospitalization were not included.Results. The study included 73450 patients aged 18 to 99 years (mean age, 73±12 years; women, 59,1%). During a median follow-up of 388 days, 16212 (22,1%) patients died. The cumulative death probability within one and five years after discharge was 16,3% and 48,9%. At each time period, the rate was higher in men when stratified by age and as age increased.The mortality rate was 15,3 (95% confidence interval 15,1 to 15,6) per 100 patientyears. For all subgroups, the highest value was recorded in the first month after discharge (50,1 per 100 patient-years), reaching a maximum in the subgroup of elderly and senile patients (60,7 per 100 patient-years).Conclusion. Within 1 year and 5 years after hospital discharge, 16,3% and 48,9% of patients with HF die, respectively. The highest death risk is typical in the first month after discharge, especially for elderly and senile patients.